CURRENT LEVELS OF DEVELOPMENT OF INTERNET TECHNOLOGIES IN TEACHING LANGUAGES - Allayarova Dilfuza Klichevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The current level of development of Internet technologies and multimedia opens up broad prospects for methods of teaching languages. Using the Web to communicate with native speakers of the target language, exchange information, watch films and programs in the Russian language, including online, becomes an integral part of the educational process and the student’s daily life. The purpose of the article is to identify the most effective ways to increase the effectiveness of the Russian language lessons.